Paddy farmer's perception and factors influencing attitude and intention on adoption of organic rice farming - Ashari; Sharifuddin, Juwaidah; Mohamed, Zainal Abidin; Terano, Rika (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
As a staple food, the availability of rice is essential for Indonesian people. It is undoubtable that Green Revolution (GR) has a significant contribution to rice production. However, GR also emerges the detrimental impact, mainly on the environment. The expectation is that organic farming is an appropriate solution for dealing with this issue. On one side, the increased in demand for healthy food implies the organic farming has a good prospect. However, the adoption rate of organic farming is still low among farmers. This study aims at examining the perceptions of paddy farmer and factor affecting attitude and behavioral intention to adopt organic rice farming. This study involved 600 paddy farmers as respondents in Sragen District, Central Java, Indonesia. The study grouped the respondents into two categories, i.e., semi-organic and conventional farmers. The data were collected through a structured questionnaire. The results showed that the perceived usefulness, perceived ease, and environmental concern affected positive and significantly on attitude. Meanwhile, the behavioral intention was influenced significantly by attitude, subjective norm, moral obligation and perceived behavioral control. Conclusively, the perceptions on technology characteristic, environmental concern, moral obligation have a positive impact on attitude and intention to adopt organic rice farming. Therefore, the dissemination of organic rice technology should be accelerated to take the advantages of positive attitudes by changing their mindset toward adopting organic rice farming.